Duration-Specific Peak Acceleration Demands During Professional Female Basketball Matches - Roell, Mareike; Helwig, Janina; Gollhofer, Albert; Roecker, Kai (Frontiers in Sports and Active Living, 2020)
Purpose: Describing the most intense periods of match-play is important in player monitoring and the development of specific training programs. The aim of this study was to extract maximum accelerations during basketball match-play and describe those as a function over time durations. Methods: Twelve professional female basketballers were monitored during 13 official matches to calculate acceleration profiles. Moving medians of time durations ranging from 0.3 to 1,800 s were computed to extract peak acceleration and deceleration magnitudes for the resultant (|accres|), horizontal (|acchor|), and vertical (|accvert|) planes. The relationship between peak magnitudes and time durations was modeled by an exponential function. Distinct curve characteristics can be described by the function parameters scale and decrease rate, which refer to an athlete's ability to perform maximum acceleration intensities over short-time (scale) and middle-time intervals (decrease rate). Generalized linear mixed-models were calculated to determine plane-specific differences in acceleration and deceleration capacities. Results: Function parameters differed significantly between |accres|, |acchor| and |accvert| [effect size (ES) = 0.33–1.15]. Comparisons within each movement plane revealed significant differences between positive and negative |accres| for the parameters scale (ES = 0.34) and decrease rate (ES = 0.39). All function parameters differed significantly between |accvert|+ and |decvert| (ES = 0.39–0.71). Rank analyses between players revealed significant inter-individual differences for all function parameters in all groups. Conclusions: Modeling peak acceleration magnitudes as a function over log-transformed time durations provides an opportunity to systematically quantify the most intense periods of match-play over short, middle and long time intervals (0.3–1,800 s). Detailed knowledge about these periods may positively contribute to training prescriptions, which intend to prepare players for highest intensities experienced during match-play in order to improve performance and prevent injuries. Derived function parameters allow inter-individual comparisons and provide insights into players' physical capabilities. This study further examines plane-specific intensity demands of professional female basketball, emphasizing the need for coaches to prepare players for maximum decelerations in the vertical plane.